Предмет: Алгебра, автор: Chip96

x^4+6x^3-2x^2-30x+25=0

Ответы

Автор ответа: ways96
0

sqrt{6}-1-1-sqrt{6}По теореме Безу , получим:

(x-1)(x+5)(x^2+2x-5)=0, тогда

(1)x-1=0        (2)x+5=0         (3)(x^2+2x-5)=0

x=1                   x=-5                D=4+20=24

                                                                x=frac{-2+-sqrt{24}}{2}

                                                                x = sqrt{6}-1 или x = -1-sqrt{6})

Ответ:x∈{1,-5,sqrt{6}-1,-1-sqrt{6}}

Похожие вопросы